Microbiology Indoor Air Quality at Hospital During the Covid19 Pandemic - Aryatama Rahardhiman; Ririh Yudhastuti; R. Azizah (Universitas Airlangga, 2020)
Introduction: Covid19 was an acute respiratory disease with fever, cough, and out of breath as the symptoms. WHO reported that until June 21st 2020, there were 8,708,008 cases were confirmed with 461,715 number of death (CFR 5.3%). In Indonesia, there were 45,891 cases were confirmed with 2,465 number of death (CFR 37%). People who were most at risk were people who physically close contact with the Covid19 patient, including health workers. The purpose of this study was to know the microbiology indoor air quality of Covid19 patient at Hospital before and during the pandemic. Method: The study design of this research was observational cross sectional. The study was done at a Hospital in East Java on December 2019 – June 2020. The sample of this research was a ward's air in a Hospital. The research variable was the number of microbiology, temperature, and humidity of the ward of Covid19 patient that was measured 3 different points of measurement each rooms. Result and Discussion: The result showed that the average of the number of microbiology before the pandemic was about 46.31 CFU/m3 with the average of the temperature was 27.64°C and the humidity was 44.58%, while during the pandemic the number of microbiology in the air increased to 64 CFU/m3 with the average of the temperature was 27.77°C and the humidity was about 42.46%. Based on the statistic analysis, there were differences between the numbers of the microbiology before and during the pandemic in the ward of Covid19 patients (p value 0.00). Conclusion: The result showed that the number of the microbiology was increased before and during the pandemic although it was still under the quality standard. Increasing of Covid19 patient was the probably reason of the increasing the number of the indoor air microbiology. It was recommended the hospital requires to control the air quality of the treatment room by regulating air ventilation.